2017
DOI: 10.1186/s13643-017-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Effective knowledge translation approaches and practices in Indigenous health research: a systematic review protocol

Abstract: BackgroundEffective knowledge translation (KT) is critical to implementing program and policy changes that require shared understandings of knowledge systems, assumptions, and practices. Within mainstream research institutions and funding agencies, systemic and insidious inequities, privileges, and power relationships inhibit Indigenous peoples’ control, input, and benefits over research. This systematic review will examine literature on KT initiatives in Indigenous health research to help identify wise and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…Knowledge user–researcher relationships in CBPR and IKT studies disrupt the division between those who do research and those who are participants in the research. CBPR and IKT provide examples of ways to conduct research that engages with a broad range of knowledge users in ways that knowledge users themselves can define as ethical and thereby acceptable [ 78 , 79 ]. Importantly, collaborative research has been found to create opportunities for real change: involvement in research by knowledge users happens more often; the research is more likely to influence the behavior of knowledge user partners; and there is the creation of real-world applicable knowledge [ 20 ].…”
Section: Main Textmentioning
confidence: 99%
“…Knowledge user–researcher relationships in CBPR and IKT studies disrupt the division between those who do research and those who are participants in the research. CBPR and IKT provide examples of ways to conduct research that engages with a broad range of knowledge users in ways that knowledge users themselves can define as ethical and thereby acceptable [ 78 , 79 ]. Importantly, collaborative research has been found to create opportunities for real change: involvement in research by knowledge users happens more often; the research is more likely to influence the behavior of knowledge user partners; and there is the creation of real-world applicable knowledge [ 20 ].…”
Section: Main Textmentioning
confidence: 99%
“…Research groups must report on the inclusion of critical inquiry and strength-based approaches to the research analysis, including the incorporation/valuing of cultural beliefs or values into the research findings, including the involvement of Indigenous stakeholders in the analysis and interpretation of the research. Analysis and reporting supported critical inquiry and strength-based approach : The tenet of a strength-based approach is ensuring that research does not perpetuate or reaffirm stereotypical beliefs. The inclusion of Indigenous stakeholders in the analysis, interpretation, and reporting of the research may assist in reducing the risks of research interpretations and outputs that advance a theory or knowledge conceptualization based on non-evidence based understanding of Indigenous health [42]. This also includes how Indigenous stakeholders have been acknowledged in the research, including principles of equity within authorship that align with partnership research approaches and contributions of Indigenous knowledge and expertise.…”
Section: Resultsmentioning
confidence: 99%
“…The final criteria specify how research teams disseminate the research outcomes to the appropriate Indigenous stakeholders in parallel with standard pathways for research dissemination and knowledge translation. It is widely understood that “dissemination of research is essential to achieve social value.” [33] Therefore, the social value of disseminating research outcomes to Indigenous stakeholders is an effective strategy in knowledge translation and partnership [42]. This enables Indigenous stakeholders to hold researchers accountable for their research praxis within their communities as well as utilizing the information to monitor organizations and to advocate for policy change and resources. Dissemination of research outputs : Indigenous health research is relevant to Indigenous communities and organizations, policy makers, Indigenous and non-Indigenous health service providers, and clinicians as well as other research teams and the wider public.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, knowledge sharing helps communities to share their knowledge directly in modes and media that they control with other communities, without the researcher as the expert mediator of knowledge or the funding agency, which in most cases in New Zealand is the Government, accumulating knowledge that perpetuates a view that the settler state knows what is best for Indigenous Peoples (Moewaka Barnes et al 2011). The idea of sharing knowledge is informed by some powerful indigenous concepts about collective well-being, collective responsibility and collective accountability (Morton Ninomiya et al 2017). Knowledge sharing positions the knowledge gained through the direct participation of Indigenous participants as a potential collective benefit.…”
Section: Kaupapa Māori: a Decolonising Approach To Research Translationmentioning
confidence: 99%